Transcript Abundance of Photorhabdus Insect-Related (Pir) Toxin in Manduca sexta and Galleria mellonella Infections - Anaïs Castagnola; Geraldine Mulley; Nathaniel Davis; Nicholas Waterfield; S. Patricia Stock (Toxins, 2016)
In this study, we assessed pirAB toxin transcription in Photorhabdus luminescens laumondii (strain TT01) (Enterobacteriaceae) by comparing mRNA abundance under in vivo and in vitro conditions. In vivo assays considered both natural and forced infections with two lepidopteran hosts: Galleria mellonella and Manduca sexta. Three portals of entry were utilized for the forced infection assays: (a) integument; (b) the digestive route (via mouth and anus); and (c) the tracheal route (via spiracles). We also assessed plu4093-2 transcription during the course of a natural infection; this is when the bacteria are delivered by Heterorhabditis bacteriophora nematodes. Transcript abundance in G. mellonella was higher than in M. sexta at two of the observed time points: 15 and 18 h. Expression of pirAB plu4093-2 reached above endogenous control levels at 22 h in G. mellonella but not in M. sexta. Overall, pirAB plu4093-2 transcripts were not as highly expressed in M. sexta as in G. mellonella, from 15 to 22 h. This is the first study to directly compare pirAB plu4093-2 toxin transcript production considering different portals of entry.